Voluntary Adoption of Integrated Reporting and Firm Valuation: The Moderating Effect of ESG Performance - Juniarti Juniarti; Aurelia Cindy Santoso; Cynthia Felita Hermawan; Alan Darmasaputra; James Wright (Jurnal Akuntansi dan Keuangan, 2024)
This study addresses a research gap by examining the impact of the voluntary adoption of integrated reporting on company value (TOBINSQ) for companies listed on the Indonesian Stock Exchange. A purposive sampling method was used to select the sample, which included companies with available ESG scores from 2018 to 2022 and accessible annual reports for the same period. The final sample consists of 83 companies, totalling 299 observations. Multiple regression analysis was employed to assess the direct effects of integrated reporting and the moderating role of ESG performance (ESGSCORE) on company value. Our findings reveal that integrated reporting positively influences company value and that ESG performance significantly moderates this relationship, enhancing the benefits of integrated reporting. The results underscore the importance for companies to adopt integrated reporting and enhance ESG performance to improve market valuation. The study also suggests that promoting integrated reporting and ESG disclosures can enhance market transparency and accountability. Future research should focus on longitudinal studies, sector-specific analyses, geographical variations, and the role of digital technologies in integrated reporting and ESG performance to provide deeper insights and practical recommendations.